2012
DOI: 10.1155/2012/782624
|View full text |Cite
|
Sign up to set email alerts
|

Potential Consequences of Abandonment in Preschool-Age: Neuropsychological Findings in Institutionalized Children

Abstract: Abstract.Objective: Several longitudinal studies had shown that early deprivation and institutionalization during the first six months of life affects the emotional, cognitive, social and neurophysiologic development. Nevertheless, our understanding of possible similar effects of delayed institutionalization, in preschool-age remains unclear to this day. The goal of this study is to evaluate the cognitive performance of institutionalized children with history of preschool-age physical abandonment. Method: 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…A study that aimed to compare the scholar performance between a group that lived with their family and another group of institutionalized children concluded that this last one showed lower averages. This result confirms that the family plays an important role in the scholar development of the children 7,16 . The children of these three researched groups showed a big number of SP, however, it is valid to highlight that these substitutive processes were in some cases synonyms of the target-word.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A study that aimed to compare the scholar performance between a group that lived with their family and another group of institutionalized children concluded that this last one showed lower averages. This result confirms that the family plays an important role in the scholar development of the children 7,16 . The children of these three researched groups showed a big number of SP, however, it is valid to highlight that these substitutive processes were in some cases synonyms of the target-word.…”
Section: Discussionsupporting
confidence: 81%
“…However, until now only a little is known about the specific aspects which interfere in the preschool period of these children 7 .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%
“…As suggested in earlier studies, attachment processes apparently contribute to the development of attention skills and of emotional and behavioral self-control. Children with early attachment deprivation are therefore at risk of exhibiting behavioral problems later on, in particular ADHD symptoms [5,11,71]. It should be noted that the adoptees in the current study may have experienced deprivation in a broader sense, not only having missed out on stable attachment relationships but also having lacked essential ingredients needed for healthy physical, emotional and cognitive development (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children who have experienced orphanage care scored worse on sustained attention tasks-for example, they had more omissions errors and slower reaction times (Loman et al, 2013;McDermott et al, 2012)-and they displayed deficits in spatial working memory, planning, visual attention, and motor inhibition (Hanson et al, 2013;Pollack et al, 2010). Studies examining other executive skills, such as concept formation, have revealed conflicting results, with some studies showing worse performance compared with nonadopted peers (Cardona et al, 2012;Hanson et al, 2013) and other studies (Pollack et al, 2010) showing no significant difference.…”
Section: Associations Between Inattentive= Overactive Behaviors and Omentioning
confidence: 99%